2020
DOI: 10.3390/foods9010089
|View full text |Cite
|
Sign up to set email alerts
|

Zymomonas mobilis in Bread Dough: Characterization of Dough Leavening Performance in Presence of Sucrose

Abstract: Zymomonas mobilis, because of its fermentative metabolism, has potential food applications in the development of leavened baked goods consumable by people with adverse responses to Saccharomyces cerevisiae. Since Z. mobilis is not able to utilize maltose present in flour, the effect of sucrose addition (2.5 g/100 g flour) on bread dough leavening properties was studied. For comparison purposes, leavening performances of S. cerevisiae with and without sucrose were also investigated. Doughs leavened by Z. mobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
0
8
1
Order By: Relevance
“…Musatti et al [7] reported that with a lower inoculum (7 vs. 8 log CFU/g dough used here) and in presence of sucrose, Z. mobilis DSM 424 showed a significantly higher lag time of 7.12 h; in the same condition, the benchmark yeast S. cerevisiae, evidenced a leavening rate of around 15 mm/h and a lag time of around 3 h.…”
Section: Parametermentioning
confidence: 72%
See 2 more Smart Citations
“…Musatti et al [7] reported that with a lower inoculum (7 vs. 8 log CFU/g dough used here) and in presence of sucrose, Z. mobilis DSM 424 showed a significantly higher lag time of 7.12 h; in the same condition, the benchmark yeast S. cerevisiae, evidenced a leavening rate of around 15 mm/h and a lag time of around 3 h.…”
Section: Parametermentioning
confidence: 72%
“…Maltose, glucose and ethanol concentrations were determined through an HPLC system (L 7000, Merck Hitachi) equipped with refractive index detector [6]. Z. mobilis, Aerobic Mesophilic Count (AMC) and yeasts and moulds (Y&M) counts were carried out as previously stated [7] and reported in log colony forming units/g of dough (log CFU/g) as means and standard deviations values.…”
Section: Dough Chemical Characterization Ph Monitoring and Microbialmentioning
confidence: 99%
See 1 more Smart Citation
“…Musatti et al [ 8 ] reported that Z. mobilis strains belonging to the official DSMZ collection (Deutsche Sammlung von Mikroorganismen und Zellkulturen GmbH), grown on a medium without yeast–derived compounds, were able to efficiently leaven model doughs when glucose was added to boost the ED catabolic pathway (20 g flour, 15 mL distilled water and 2 g glucose, leavening at 29 °C). Its interesting leavening performance was also confirmed in bread-like dough formulations (333 g flour, 167 mL distilled water) added with glucose or fructose [ 9 , 10 ]. However, when employing these strains, the addition of NaCl was found to slow down the dough rising.…”
Section: Introductionmentioning
confidence: 95%
“…Similarly, there is an increasing interest of the market in “yeast-free” leavened foods, due to the recent concern about the role of S. cerevisiae (particularly its anti-antibodies) in several pathologies, including Crohn’s disease, gastro-esophageal reflux, acne inversa and gut fermentation syndrome [ 20 , 21 , 22 , 23 ]. In this context, processes to develop “yeast-free” bakery products have been formulated and applied at the industry level [ 24 , 25 , 26 ]. In particular, we developed a protocol based on the use of a liquid sourdough started with a single bacterial strain for “yeast-free” bread and focaccia production, obtaining products with improved functional/nutritional characteristics compared to those made with baker’s yeast [ 24 , 27 ].…”
Section: Introductionmentioning
confidence: 99%